(3TYQ LQjQs - (3LQjQ , LQjQ Hf YWjg Hf MPjag GdNWaj Hf HOQ GdcdHj GdjQHhYj,J (B110 (3g` s ((3EHQGgje Hf ESMGb (B((3hQGb GdeHQO(B) s)
(3ChdgG (B:s
(3bGd LQjQ YWjI Hf GdNWai Mi GdZOGI HQGeI GdGWdGd QSeG JMed CgdI aGMGdG s
(3BNQgG (B:s
(3ajBHf GdCcQejf EPG fSHJe hai GdCcQejf Ef oMSH GdYOjO s
(3GdfSNI HgG MhGTs
(3QhGjI CHj GdMSf eMeO Hf GGdYHGS Hf CMeO Hf GdaQGJ Yf CHjg Yf CHj SYjO Hf GdMSjf GdScQis
(3Yf CHj LYaQ eMeO Hf MHjH SeGM CHj GdZfGje eMeO Hf CMeO Hf YeQ GdNdGds
(3hHOGNdgG Jedc eDQN ai (B989(3g`s
(3hGdfSNI ebGHdI s
(3hQO CjVkG JMJ Qbe (B"831(3,(B832(3,(B877(3,(B1020 -1022(3,(B2399" s
Keywords: (3GdCOHs